A method of eddy-current testing of bars and tubes based on the eddy currents with different frequencies of circular and longitudinal directions excitation; The 7th International Forum on Strategic Technology (IFOST-2012), September 18-21, 2012, Tomsk - Goldstein (Goldshtein) A. E. Aleksandr Efremovich; Bulgakov V. F. Valery Fedorovich; Kroning H.-M. V. A.; Belyankov V. Y. (2012, 2012)
Title screen